First record of benthic diatoms (Bacillariophyceae and Fragilariophyceae) from Isla Guadalupe, Baja California, Mexico - Francisco Omar López-Fuerte; David A. Siqueiros-Beltrones; Ricardo Yabur (Revista Mexicana de Biodiversidad)
Guadalupe Island represents a unique ecosystem. Its volcanic origin and remoteness from the Baja California peninsula have allowed for the successful establishment of its distinctive flora and fauna. However, the difficulty in accessing the island has precluded the study of its biotic communities, mainly the marine ones. Consequently, no studies on benthic or planktonic diatoms have been hitherto published. Thus, the first records of marine benthic diatom species (epiphytic, epilithic, epizoic) from Guadalupe Island in the NW Mexican Pacific are here provided. One hundred and nineteen diatom taxa belonging to the Bacillariophyceae and Fragilariophyceae were identified, including species and varieties. The former with 87 taxa was the most diverse. Thirteen taxa are new records for Mexico; photographic images of these are provided. Because this is the first study for the benthic diatoms of Isla Guadalupe, a particular bio-geographical affinity is not proposed. However, the best represented genus was Mastogloia which has tropical affinity, and Cocconeis thalassiana was also identified, a new species recently recorded for the Mexican Caribbean.